DEVELOPMENT OF PASTERIZATION MODES FOR HIGH-SUGAR CANS IN CONTINUOUS ACTING PASTEURIZERS - G. P. Pokudina; M. V. Trishkaneva; R. A. Volkova (Пищевые системы, 2019)
High-sugar canned fruits, such as jam, marmalade, confiture, are characterized by a high content of soluble dry solids and high acidity, which allows to apply to them pasteurization processes as heat treatment. In comparison with sterilization processes, heat treatment of hermetically sealed canned food during pasteurization is implemented at temperatures less than 100°C.The article presents the results of the development of scientifically-based pasteurization modes for high-sugar canned food for industrial continuous-acting pasteurizers (CAP — continuous-acting pasteurizers) of open type with a temperature in the heating area less than 100°C. For today, such pasteurizers are widely spread due to the simplicity of their design, high productivity, with the option to reduce consumption of water, steam, electricity and to use it for the various types of packaging. So, the actual task of this article is the establishment of canned fruit pasteurization modes for such pasteurizers.The development of pasteurization modes for high-sugar canned food using strawberry jam as a sample was carried out in the experimental equipment simulating the operation of a continuous-acting pasteurizer. The studies were implemented to confirm that the developed modes of heat treatment in the CAP as a matter of fact provide industrial sterility of the produced high-sugar canned food. Optimal pasteurization modes have the following parameters: heat treatment in an autoclave sterilizer at a heating temperature of the heating medium 97°C and stage-by-stage cooling of the products with water at temperatures 70°C, 50°C and 30°C.